Interaction between FGFR-2, STAT5, and progesterone receptors in breast cancer - Cerliani, Juan Pablo (2011)
Fibroblast growth factor (FGF) receptor 2 (FGFR-2) polymorphisms have been associated with an increase in estrogen receptor and progesterone receptor (PR)-positive breast cancer risk; however, a clear mechanistic association between FGFR-2 and steroid hormone receptors remains elusive. In previous works, we have shown a cross talk between FGF2 and progestins in mouse mammary carcinomas. To investigate the mechanisms underlying these interactions and to validate our findings in a human setting, we have used T47D human breast cancer cells and human cancer tissue samples. We showed that medroxyprogesterone acetate (MPA) and FGF2 induced cell proliferation and activation of ERK, AKT, and STAT5 in T47D and in murine C4-HI cells. Nuclear interaction between PR, FGFR-2, and STAT5 after MPA and FGF2 treatment was also showed by confocal microscopy and immunoprecipitation. This effect was associated with increased transcription of PRE and/or GAS reporter genes, and of PR/STAT5-regulated genes and proteins. Two antiprogestins and the FGFR inhibitor PD173074, specifically blocked the effects induced by FGF2 or MPA respectively. The presence of PR/FGFR-2/ STAT5 complexes bound to the PRE probe was corroborated by using NoShift transcription and chromatin immunoprecipitation of the MYC promoter. Additionally, we showed that T47D cells stably transfected with constitutively active FGFR-2 gave rise to invasive carcinomas when transplanted into NOD/SCID mice. Nuclear colocalization between PR and FGFR-2/STAT5 was also observed in human breast cancer tissues. This study represents the first demonstration of a nuclear interaction between FGFR-2 and STAT5, as PR coactivators at the DNA progesterone responsive elements, suggesting that FGFRs are valid therapeutic targets for human breast cancer treatment. ©2011 AACR.